2005
DOI: 10.1207/s15324796abm2903_10
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of positive meaning and vulnerability following breast cancer: Predictors and outcomes among long-term breast cancer survivors

Abstract: Results suggest that a cancer diagnosis may lead to enduring feelings of vulnerability as well as positive changes in meaning; however, these perceptions have very different mental health correlates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
200
1
14

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(232 citation statements)
references
References 42 publications
17
200
1
14
Order By: Relevance
“…These include enhanced self-esteem, greater life appreciation and meaning, heightened spirituality, and greater feelings of peace and purposefulness. 32,43,44 These positive long-term or late effects can be viewed as benefits of cancer diagnosis and treatment and are often characterized as posttraumatic growth. [45][46][47][48] Finally, although we have drawn a distinction between 'long-term' and 'late' psychological effects, the research literature generally has not.…”
Section: Psychological Long-term and Late Effects Of Cancermentioning
confidence: 99%
“…These include enhanced self-esteem, greater life appreciation and meaning, heightened spirituality, and greater feelings of peace and purposefulness. 32,43,44 These positive long-term or late effects can be viewed as benefits of cancer diagnosis and treatment and are often characterized as posttraumatic growth. [45][46][47][48] Finally, although we have drawn a distinction between 'long-term' and 'late' psychological effects, the research literature generally has not.…”
Section: Psychological Long-term and Late Effects Of Cancermentioning
confidence: 99%
“…Some 20 scales were identified that measured meaning: the Chinese Cancer Coherence Scale (CCCS) (Chan et al, 2007); the Constructed Meaning Scale (Fife, 1995); the meaning/peace subscale of the Functional Assessment of Chronic Illness Therapy -Spiritual Well-Being Scale (FACIT-Sp) (Canada et al, 2008;Murphy et al, 2010;Peterman et al, 2002); the Illness Cognitions Questionnaire (ICQ) (Evers et al, 2001); the Internal Coherence Scale (ICS) (Kroz et al, 2009); the Life Attitude Profile (LAP)/ Life Attitude Profile -Revised (LAP -R) (Reker, 1992;Reker & Peacock, 1981); the Life Evaluation Questionnaire (LEQ) (Salmon et al, 1996); the Meaning in Life questions (including the Benefit Finding Scale [BFS]) used by Tomich and Helgeson (2002); the Meaning in Life Questionnaire (MLQ) (Steger et al, 2006); the Meaning in Life Scale (MILS) (Jim et al, 2006); the Meaning in Suffering Test (MIST) (Starck, 1983); the Perceived Meanings of Cancer Pain Inventory (PMCPI) (Chen, 1999); the Personal Meaning Profile (PMP) (Wong, 1998); the Positive Meaning and Vulnerability Scale (Bower et al, 2005); the Purpose in Life (PIL) Test (Crumbaugh & Maholick, 1964); the Purposelessness, Understimulation, and Boredom (PUB) Scale (Passik et al, 2003); the Schedule for Meaning in Life Evaluation (SMiLE) (Fegg et al, 2008); the Sense of Coherence (SOC) Scale (Antonovsky, 1993); the Sources of Meaning Profile (SOMP)/Sources of Meaning Profile -Revised (SOMP -R) (Reker, 1996); and the World Assumptions Scale (Janoff-Bulman, 1989). The optimal measure of meaning will vary depending on the purpose and context of the assessment.…”
Section: Meaningmentioning
confidence: 99%
“…Further, the experience of stress-related growth decreases distress in cancer survivors (Bower et al, 2005;Morrill et al, 2008). Lower distress following growth might be relevant for individuals who have experienced earlier life stress along with previous growth.…”
Section: Stress-related Growth After Cancermentioning
confidence: 99%